2006
DOI: 10.1118/1.2335490
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two methods of predicting MLC leaf positions using EPID measurements

Abstract: In intensity modulated radiation treatments (IMRT),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 6 publications
3
44
0
Order By: Relevance
“…Baker et al 19 and Parent et al 14 reported that a systematic tilt of the EPIDs was observed in their studies and indicated that it was likely to occur for all different EPIDs; Clarke and Budgell 20 have also demonstrated the effect of the gantry angle on the EPID sag. Therefore, it is expected that the imaging geometry for the EPID at different gantry angles might deviate from an ideal configuration that we use as the basis for the measurement of the leaf end position.…”
Section: Iib Geometric Status Of the Epidmentioning
confidence: 99%
See 1 more Smart Citation
“…Baker et al 19 and Parent et al 14 reported that a systematic tilt of the EPIDs was observed in their studies and indicated that it was likely to occur for all different EPIDs; Clarke and Budgell 20 have also demonstrated the effect of the gantry angle on the EPID sag. Therefore, it is expected that the imaging geometry for the EPID at different gantry angles might deviate from an ideal configuration that we use as the basis for the measurement of the leaf end position.…”
Section: Iib Geometric Status Of the Epidmentioning
confidence: 99%
“…Any systematic error introduced in the MLC calibration might lead to actual leaf positions different from the expected ones, resulting in dose errors. 14 In order to circumvent this dependence and provide a universal approach of probing the actual delivery of a fluence map, we propose using an amorphous silicon electronic portal imaging device ͑aSi-EPID͒ to capture every segment of the fluence map during the treatment. For each captured segment, the leaf positions for each pair of leaves are found by an edge detection algorithm; the fractional monitor unit ͑fMU͒ associated with this particular segment is also sampled.…”
Section: Introductionmentioning
confidence: 99%
“…Using the images of the square field, the collimator angle and the tilt of the EPID detector were corrected. 18 Gantry angle was 0°for all measurements.…”
Section: Iib Imager and Acceleratormentioning
confidence: 99%
“…The leaf positions for each pair were determined at the 50% of the intensity profile formed by the pair. 18 The leaf positions on the EPID images were determined using the same method as the one used for film. The leaf positions measured with the film and EPID were compared to determine the accuracy of the VORTE.…”
Section: Iic Measurement Of the Accuracy Of The Vortementioning
confidence: 99%
“…The electronic portal imaging device (EPID) is a dependable system when corrections are made for systematic tilts and shifts [7,8] and when image sagging due to gantry angle [9] has been taken into account. A significant number of researchers have investigated MLC QA by film or EPID [7][8][9][10][11][12][13] to measure the accuracy of the MLC controller independently and ensure that the MLC edge positions agree with the radiation field edges to within 0.3 mm [14]. EPID measurements are highly reproducible, with a standard deviation of ,0.1 mm for individual leaf/collimator positions and ,0.05 mm for a 10610 cm 2 field [7].…”
mentioning
confidence: 99%